Probit Analysis of Women’s Access to Agricultural Inputs in Bosso Local Government Area, Niger State, Nigeria - R S Olaleye; M Ibrahim; M A Ojo (Journal of Agricultural Extension, 2009)
The title of the study is Probit analysis of women’s access to agricultural inputs in Bosso Local Government Area of Niger State, Nigeria. The specific objectives are to identify the socio-economic characteristics of the women farmers and examine their sources of agricultural inputs as well as their accessibility to these inputs, including problems they faced in accessing the inputs. To achieve these, a total of 140 women farmers were purposively selected from 10 wards of the LGA. Validated Interview Schedule with reliability coefficient of 0.87 was used to collect relevant data from the respondents. Findings revealed that majority of the women farmers were within active productive age of between 21 and 50 years, mostly without formal education (64.3%) and married(81.4%).Also, most of the women engaged in farming either as a full or part time farmers. Similarly, few women had regular access to credit facilities and fertilizer .The problem adduced by the women farmers were discrimination against them and poor rural roads. Furthermore, probit analysis showed that 64% variation in the adequacy of inputs purchased by the women farmers was significantly explained by their access to labour, fertilizer, agro-chemicals and distance between individual farms and points of sales of agricultural inputs .It is recommended that women farmers should be encouraged to form co-operative groups in order to enhance their access to relevant inputs. Similarly, the Local Government Authority should try and rehabilitate the existing rural roads in addition to the construction of other roads with a view to linking the various villages and towns for easy transportation